Accelerating targeted mosquito control efforts through mobile West Nile virus detection - Zsaklin Varga; Rubén Bueno-Marí; José Risueño Iranzo; Kornélia Kurucz; Gábor Endre Tóth; Brigitta Zana; Safia Zeghbib; Tamás Görföl; Ferenc Jakab; Gábor Kemenesi (Parasites & Vectors, 2024)
Abstract Background Different mosquito control strategies have been implemented to mitigate or prevent mosquito-related public health situations. Modern mosquito control largely relies on multiple approaches, including targeted, specific treatments. Given this, it is becoming increasingly important to supplement these activities with rapid and mobile diagnostic capacities for mosquito-borne diseases. We aimed to create and test the applicability of a rapid diagnostic system for West Nile virus that can be used under field conditions. Methods In this pilot study, various types of adult mosquito traps were applied within the regular mosquito monitoring activity framework for mosquito control. Then, the captured specimens were used for the detection of West Nile virus RNA under field conditions with a portable qRT-PCR approach within 3–4 h. Then, positive samples were subjected to confirmatory RT-PCR or NGS sequencing in the laboratory to obtain genome information of the virus. We implemented phylogenetic analysis to characterize circulating strains. Results A total of 356 mosquito individuals representing 7 species were processed in 54 pools, each containing up to 20 individuals. These pools were tested for the presence of West Nile virus, and two pools tested positive, containing specimens from the Culex pipiens and Anopheles atroparvus mosquito species. As a result of subsequent sequencing, we present the complete genome of West Nile virus and Bagaza virus. Conclusions The rapid identification of infected mosquitoes is the most important component of quick response adulticide or larvicide treatments to prevent human cases. The conceptual framework of real-time surveillance can be optimized for other pathogens and situations not only in relation to West Nile virus. We present an early warning system for mosquito-borne diseases and demonstrate its application to aid rapid-response mosquito control actions. Graphical Abstract